AN EVALUATION OF SCHOLARLY WORKS IN ZAKAT: A BIBLIOMETRIC ANALYSIS OF ISLAMIC ECONOMICS JOURNALS IN INDONESIA - Egi Arvian Firmansyah; Amelia Rizky Alamanda; Teguh Santoso (Univeristas Islam Bandung, 2020)
Zakat is one of the pillars of Islam and an Islamic social instrument to reduce poverty Also, the research about it has been conducted worldwide. However, none of the researchers has primarily evaluated the literature of zakat using bibliometric analysis. Using VOSviewer software to 280 journal articles published in six Islamic economics journals in Indonesia, this research aims to evaluate the scholarly works specifically in zakat in Indonesia. The results of this study show that the AL-IQTISHAD journal is the one published in most articles in zakat. Hence, those who are interested in publishing articles in zakat may select this journal. Besides, the maps based on co-occurrence keyword and title show that zakat is a less popular topic in Islamic economics journals in Indonesia.